Understanding how the message appeal of moral beauty influences advertising effectiveness under mortality salience. Issue 6 (18th August 2019) - Wu, Linwan
Abstract: Consumers may be reminded of life mortality by some life events and media content. Mortality salience as a contextual factor has not been sufficiently investigated in the existing literature of advertising. The present research analyzes how the interplay between mortality salience and moral beauty influences consumers' perceptions of life meaning and their responses to advertisements. Results of two studies confirmed that participants perceived increased life meaning when viewing advertisements that presented moral beauty. In Study 1, participants who were reminded of death evaluated an advertisement that presented moral beauty more favorably than an advertisement without such content. In Study 2, younger (i.e., age 18–25) and older participants (i.e., 55 and above) were recruited and the results indicated that the phenomenon observed in Study 1 was only prominent among younger participants. These results are believed to provide interesting insights to marketing communication both theoretically and practically.